Filsafat Ilmu Tafsir: Ontologi, Epistemologi, dan Aksiologi dalam Studi Islam Kontemporer - Haryanto Haryanto (ANWARUL, 2026)
Although the philosophy of Qur’anic exegesis has received attention in Islamic studies, scholarship that specifically discusses the integration of ontological, epistemological, and axiological dimensions in contemporary exegesis remains limited. This study aimed to analyze how the philosophy of ʿilm al-tafsīr positions Qur’anic interpretation not only as a scholarly process but also as a spiritual and humanistic process. The study employed a qualitative approach with a library research design through a review of Qur’anic verses, classical and contemporary exegetical works, and literature on Islamic philosophy of science. Data were drawn from primary sources, namely the Qur’an and major tafsir texts, and were analyzed using content analysis and a comparative method. The findings indicate that ʿilm al-tafsīr ontologically functions to understand the essence of human existence and revelation; epistemologically, it operates as a synthesis of revelation and reason in constructing sound knowledge; and axiologically, it directs knowledge toward maṣlaḥah, morality, and divine values. These findings contribute to the development of an Islamic scientific paradigm and broaden understanding of tafsir as an integral discipline that integrates theoretical and practical dimensions. The study concludes by emphasizing the importance of the philosophy of ʿilm al-tafsīr in building an integral, dynamic Islamic scientific paradigm that is relevant to modern challenges, and it recommends that Islamic educational institutions integrate philosophical approaches into tafsir curricula. The implications include a theoretical contribution to enriching the literature on Islamic philosophy of science and practical implications for developing contemporary tafsir methodologies that balance fidelity to the text with contextual relevance.